Os efeitos das fontes e formas dos nudges de normas sociais sobre o gerenciamento de resultados das empresas no processo de tomada de decisão contábil - Moreira, Caritsa Scartaty (2023)
This study aimed to analyze the effects of the sources and forms of social norms nudges on earnings management in the accounting decision-making process. In exploring this relationship, we sought grounding in literature that considers earnings management as an aggressive practice in reporting accounting information. In the context of accounting decision-making, various factors determine the level of earnings management by management and their team, including the social norms followed by the organizational hierarchy, either from the top tone or from peers. Considering that social norms affect decision-makers' behavior regarding accounting standards, nudges were used to guide accounting professionals towards lower levels of earnings management. Nudges, also called pushes, are tools that modify choice architecture to guide people's behavior without significantly affecting economic incentives, while preserving freedom of choice. The study was classified as a randomized experiment of the betweensubjects type. The analysis was based on a 2x2+1 factorial experiment, with two conditions for the source of nudges (top tone or peer tone) and two conditions for the forms of nudges (popup or fixed message), and one control condition, resulting in five groups. The final sample consisted of 362 accountants. The dependent variable in the study addressed the level of earnings management, and the independent variables included the different sources of nudges (top or peers) along with the forms of nudges (pop-up or fixed message). For data analysis and interpretation, descriptive statistics, Analysis of Variance (ANOVA), and Structural Equation Modeling were used. The results indicated that the presence of social norms nudges, regardless of the source and form, was statistically significant in reducing the level of earnings management compared to the absence of these nudges. Remarkably, nudges issued by leaders in the form of fixed messages demonstrated a statistically more significant effect compared to other sources and forms of nudges. With the results suggesting a statistically more significant impact of the top tone in reducing earnings management, a possible explanation is that, in the mediation analysis, only nudges issued by leaders were able to effectively activate social norms. Thus, even if peers convey messages about accounting norms and influence the decisionmaking of colleagues at the same hierarchical level, participants may interpret them as reflecting typical leader behavior. When analyzing the effects between the sources and forms of nudges, without considering participants who were not exposed to nudges, no statistically significant differences in earnings management were found between nudges issued by leaders and peers, nor between the communication forms of pop-up and fixed message. Thus, statistically, both sources and forms seem to produce similar effects in reducing earnings management, demonstrating the versatility of the application of social norms nudges in the organizational context. The results of this research contribute to the expansion of literature seeking mechanisms that promote informational quality. They also contribute to verifying the effects of applying nudges in a new context, accounting decision-making. In practical terms, the contributions extend to owners and managers, as they can use norm-based intervention techniques to influence the team responsible for preparing financial statements. Suggesting the application of social norms nudges in the accounting system, adapting them to the organizational context, and testing the effects of hierarchical structure demonstrated the potential impact of this tool, reducing earnings management.